Enhanced thermopower of graphene films with oxygen plasma treatment - Ajayan, Pulickel M. (2012)
In this work, we show that the maximum thermopower of few layers graphene (FLG) films could be greatly enhanced up to ∼700 μV/K after oxygen plasma treatment. The electrical conductivities of these plasma treated FLG films remain high, for example, ∼104 S/m, which results in power factors as high as ∼4.5 x 10-3 W K-2 m-1. In comparison, the pristine FLG films show a maximum thermopower of ∼80 μV/K with an electrical conductivity of ∼5 x 104 S/m. The proposed mechanism is due to generation of local disordered carbon that opens the band gap. Measured thermopowers of single-layer graphene (SLG) films and reduced graphene oxide (rGO)